Mixed layer depth values for the n = 1968 modern dinocyst database extracted from the monthly climatology by de Boyer Montégut (2023) - Xiner Wu (PANGAEA, 2025)
Monthly, seasonal and annual mixed layer depth (MLD) values at the 1968 sites of the modern dinocyst database by de Vernal et al. (2020). The MLD values were extracted from the monthly climatology based on profile data of 1970-2021 by de Boyer Montégut (2023) using a density threshold of 0.03 kg/m3 with reference to 10 m depth. In order to get an MLD value that corresponds to each site, the MLD climatology products were interpolated to the previously published 1968 sites.
In: Wu, X (2025): Mixed layer depth values for the n = 1968 modern dinocyst database [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.982265